CLINICAL CASE ADRENOGENITAL SYNDROME - Yerokhovych, V.M.; Bobryk, M.l. (The Ukrainian Scientific Medical Youth Journal, 2017)
The article describes clinical case Adrenogenital syndrome in child study hormonal and physical state which facilitated the correct treatment and solving legal issues for further life through legal sex change. At birth, the child is registered in the male sex. At the age of 17 days hospitalized due to the crisis adrenal insufficiency examined, manifested signs hypercorticism moon face, available malformation of the external genitalia - the degree of virilization in Prader- III. Diagnosed with congenital adrenal dysfunction, salt-losing form. Karyotype 46, XX. The main indicator of Adrenogenital syndrome screening on 17-oksiprogesterona 25.50 ng I ml (30.09.2016) at the reference sense 0.23-0.75 ng I mL. Pathogenetic therapy initiated in hospital preparations of glucocorticoids - kortef 7.5 mg per day and mineralocorticoid - kortyneff 0.01 mg per day. The level of 17-OHP decreased to 5.15 ng I ml (10/ 14/2016). Laboratory findings functional state of adrenal glands also changed. Fluid and electrolyte balance restored. The results of ultrasound pelvic area: displays internal female sex organs.According to the medical consultation, further treatment plan consisted of hormone replacement therapy, correction fluid and electrolyte balance and corrective plastic external genitalia routinely. The recommended change to female sex civil (with written consent of parents).